Elevated SAA1 promotes the development of insulin resistance in ovarian granulosa cells in polycystic ovary syndrome - Qinling Zhu; Yue Yao; Lizhen Xu; Hasiximuke Wu; Wangsheng Wang; Yaqiong He; Yuan Wang; Yao Lu; Jia Qi; Ying Ding; Xinyu Li; Jiaan Huang; et al. (BMC, 2022)
Abstract Background Insulin resistance (IR) contributes to ovarian dysfunctions in polycystic ovarian syndrome (PCOS) patients. Serum amyloid A1 (SAA1) is an acute phase protein produced primarily by the liver in response to inflammation. In addition to its role in inflammation, SAA1 may participate in IR development in peripheral tissues. Yet, expressional regulation of SAA1 in the ovary and its role in the pathogenesis of ovarian IR in PCOS remain elusive. Methods Follicular fluid, granulosa cells and peripheral venous blood were collected from PCOS and non-PCOS patients with and without IR to measure SAA1 abundance for analysis of its correlation with IR status. The effects of SAA1 on its own expression and insulin signaling pathway were investigated in cultured primary granulosa cells. Results Ovarian granulosa cells were capable of producing SAA1, which could be induced by SAA1 per se. Moreover, the abundance of SAA1 significantly increased in granulosa cells and follicular fluid in PCOS patients with IR. SAA1 treatment significantly attenuated insulin-stimulated membrane translocation of glucose transporter 4 and glucose uptake in granulosa cells through induction of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) expression with subsequent inhibition of Akt phosphorylation. These effects of SAA1 could be blocked by inhibitors for toll-like receptors 2/4 (TLR 2/4) and nuclear factor kappa light chain enhancer of activated B (NF-κB). Conclusions Human granulosa cells are capable of feedforward production of SAA1, which significantly increased in PCOS patients with IR. Excessive SAA1 reduces insulin sensitivity in granulosa cells via induction of PTEN and subsequent inhibition of Akt phosphorylation upon activation of TLR2/4 and NF-κB pathway. These findings highlight that elevation of SAA1 in the ovary promotes the development of IR in granulosa cells of PCOS patients.